Environmental and economic cost analysis of housing in temperate climate using an innovative lightweight partitioning system - Mendonça, Paulo (2017)
This paper presents an economic and environmental cost analysis of a representative Portuguese housing dwelling unit using an innovative lightweight adjustable membrane partitioning system, developed within a research project. The environmental and economic costs of this system, both on the construction and occupancy phases, were compared with the Portuguese conventional dividing wall solution, in hollow brick, simulated on the same reference dwelling, using the same layout and remaining constructive elements. The occupancy phase costs were evaluated by computer simulation, which allowed determining how the occupancy schedule of daytime and night time occupied areas may influence the cooling and heating needs for different solar orientations.